OPTIMIZATION OF ENZYME-MICROWAVE ASSISTED EXTRACTION, CHARACTERIZATION AND ANTIOXIDANT ACTIVITY OF POLYSACCHARIDE FROM Ganoderma lucidum - Lira Windriawati Listriyani; Sumi Hudiyono; Rudiyono Rudiyono; Siti Zulaeha; Ahmad Wibisana (BRIN - Badan Riset dan Inovasi Nasional, 2023)
Enzyme-Microwave Assisted Extraction (EMAE) is a new process for extracting Ganoderma lucidum polysaccharides (GLPs). Cellic® CTec2 was chosen as an enzyme that assists in microwave extraction. The four variables involved in this study were enzyme concentration (%), enzymatic reaction time (minutes), solvent-to-solid ratio (mL/g), and microwave extraction time (minutes). This study showed that the enzyme concentration and solvent-to-solid ratio had a significant effect on the response in the range studied. Yield extraction of polysaccharides from experiments conducted at optimum conditions showed good agreement with the predictions from the model. The EMAE method showed a higher polysaccharide extraction yield than hot water extraction (HWE) method. GLPs from EMAE method had antioxidant activity of 79.47 ± 0.71% (DPPH) and 0.884 ± 0.013 mM Fe2+/L (FRAP), where these values were higher than those of the HWE method.